2022
DOI: 10.3389/fmicb.2021.795555
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi’s Sarcoma-Associated Herpesvirus, but Not Epstein-Barr Virus, Co-infection Associates With Coronavirus Disease 2019 Severity and Outcome in South African Patients

Abstract: In South Africa, the Coronavirus Disease 2019 (COVID-19) pandemic is occurring against the backdrop of high Human Immunodeficiency Virus (HIV), tuberculosis and non-communicable disease burdens as well as prevalent herpesviruses infections such as Epstein-Barr virus (EBV) and Kaposi’s sarcoma-associated herpesvirus (KSHV). As part of an observational study of adults admitted to Groote Schuur Hospital, Cape Town, South Africa during the period June–August 2020 and assessed for Severe Acute Respiratory Syndrome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…Finally, a study of 104 patients in South Africa, where there is a high prevalence of herpesviruses infections, reported that coinfection with KSHV but not EBV might be associated with the severity of clinical outcomes following COVID‐19. 26 …”
Section: Sars‐cov‐2 Infection and Kshvmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, a study of 104 patients in South Africa, where there is a high prevalence of herpesviruses infections, reported that coinfection with KSHV but not EBV might be associated with the severity of clinical outcomes following COVID‐19. 26 …”
Section: Sars‐cov‐2 Infection and Kshvmentioning
confidence: 99%
“…Finally, a study of 104 patients in South Africa, where there is a high prevalence of herpesviruses infections, reported that coinfection with KSHV but not EBV might be associated with the severity of clinical outcomes following COVID-19. 26 In addition to viral coinfection, anti-COVID-19 therapies, including azithromycin, nafamostat mesylate, and remdesivir are associated with activating different cellular signaling pathways leading to viral lytic reactivation. 23,27 Azithromycin, an antibiotic for treatment of bacterial infections, effectively upregulated mitogenactivated protein kinases (MAPKs) signaling activities to mediate lytic reactivation.…”
mentioning
confidence: 99%
“…Since covid 19, several studies have demonstrated the action of SARS Cov 2 on the reactivation of the HHV 8 virus hence the increased prevalence of Kaposi's sarcoma. They even found that the quality of life of patients with Kaposi's sarcoma infected with SARS Cov 2 without HIV infection is lower than those infected with HIV [1,6].…”
Section: Discussionmentioning
confidence: 99%
“…The severity lies in acute respiratory distress syndrome and multi-organ failure. In addition, several skin manifestations have also been widely documented including frostbite-like lesions, erythema multiforme and maculopapular lesions [1].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a previous study did not show increased disease severity in individuals with coinfection of EBV and SARS‐CoV‐2 and the results demonstrated no differences in terms of viral load and disease outcome. 15 On the other hand, EBV coinfection was associated with increased incidence of fever, higher aspartate aminotransferase and C‐reactive protein values, and corticosteroid use compared to SARS‐CoV‐2 infection alone in another study by Chen et al 6 EBV reactivation was also associated with a longer duration of Intensive care unit stay. 16 However, stringent care is advised in evaluating the evidence of the causal association of EBV with COVID‐19 severity or long COVID symptoms, considering the potential confounding effects of the high prevalence of EBV in the general population and the reactivation of other latent viruses in patients, such as herpes simplex virus, cytomegalovirus, Varicella zoster virus (VZV), human herpes virus‐6 (HHV‐6), and human herpes virus‐7 (HHV‐7).…”
Section: Figurementioning
confidence: 99%